Numerical evaluation of a full‐wave antenna model for near‐field applications. Issue 2 (1st October 2012) - Tran, A.P.; Warren, C.; André, F.; Giannopoulos, A.; Lambot, S.
ABSTRACT: In this study, we numerically evaluated a full‐wave antenna model for near‐field conditions using a Finite‐Difference Time‐Domain (FDTD) antenna model. The antenna is effectively characterized by a series of source and field points and global reflection/transmission coefficients, which by using analytical solutions of Maxwell's equations, enable us to significantly reduce computation times compared to numerical approaches. The full‐wave GPR model was calibrated by a series of radar data from numerical measurements performed above an infinite perfect electrical conductor (PEC). The calibration results provided a very good agreement with data from the FDTD antenna model giving a correlation coefficient of 0.9995. The model was subsequently verified by using it to invert responses from the FDTD antenna model to reconstruct the electrical properties of an artificial medium subject to 8 scenarios of layering, thickness and electrical properties. Full‐wave inverse modelling enabled us to very well reproduce the GPR data both in time and frequency domains, resulting in accurate estimations of the dielectric permittivity even with a two‐layered medium with highly contrasting electrical properties. The relative errors of the permittivity estimation were less than 5% for all medium scenarios and antenna heights. Inversion also provided very good estimations of the electrical conductivity when this parameter was relatively high but poor results were obtained for low conductivities. Surface response analysis showed that the model was more sensitive to permittivity than conductivity and more sensitive to high than low conductivities. Our modelling approach shows great potential to apply full‐wave inversion for retrieving the electrical properties of the subsurface from near‐ and far‐field radar measurements.